SYNTHESIS, Cu(II) SCHIFF BASE COMPLEXATION AND STRUCTURAL ANNALYSIS OF THE LIGAND 4-{[2-(METHOXYCARBONYL)PYRROLIDIN-1-YL]METHYL}BENZOIC ACID - H., . Far1, . Benaissa T.; S ., . Daoudi . (university of eloued جامعة الوادي, 2020)
A new prolineA new prolineA new proline A new proline A new proline -based ligand was synbased ligand was synbased ligand was syn based ligand was syn based ligand was syn based ligand was syn based ligand was syn based ligand was syn based ligand was syn based ligand was syn thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was thesized by a convenient procedure. The ligand was characterized by characterized by characterized by characterized by characterized by characterized by characterized by characterized by characterized by characterized by 1H NMR, H NMR, H NMR, H NMR, 13 C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base C NMR and IR spectroscopies. Copper (II) Schiff base complexes of 4complexes of 4 complexes of 4complexes of 4 complexes of 4 complexes of 4 complexes of 4complexes of 4-{[2 -(methoxycarbonyl) pyrrolidin (methoxycarbonyl) pyrrolidin(methoxycarbonyl) pyrrolidin (methoxycarbonyl) pyrrolidin(methoxycarbonyl) pyrrolidin (methoxycarbonyl) pyrrolidin (methoxycarbonyl) pyrrolidin(methoxycarbonyl) pyrrolidin (methoxycarbonyl) pyrrolidin (methoxycarbonyl) pyrrolidin -1-yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand yl] methyl} benzoic acid of this ligand were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized were synthesized and characterized by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. by the aforementioned spectroscopy techniques, i.e. 1H NMR, 13 C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the C NMR and IR. Moreover, its bactericidal activity was assessed through the determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well idetermination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well i determination of the minimum inhibitory concentration (MIC) values as well inhibition nhibition nhibition nhibition zone diameter for gram pozone diameter for gram po zone diameter for gram pozone diameter for gram po zone diameter for gram po zone diameter for gram pozone diameter for gram po zone diameter for gram pozone diameter for gram po zone diameter for gram po zone diameter for gram po sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as sitive bacteria, such as Staphylococcus aureus Staphylococcus aureus Staphylococcus aureusStaphylococcus aureus Staphylococcus aureus Staphylococcus aureusStaphylococcus aureus , and gram negative , and gram negative , and gram negative , and gram negative , and gram negative , and gram negative , and gram negative , and gram negative , and gram negative , and gram negative bacteria like bacteria like bacteria like bacteria like bacteria like bacteria like bacteria like bacteria like Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter Klebsiella pneumoniae, Citrobacter freundii, Salmonella typhi, Enterobacter cloacaecloacae (the two bacteria (the two bacteria (the two bacteria (the two bacteria (the two bacteria (the two bacteria (the two bacteria (the two bacteria Citrobacter freundiiCitrobacter freundii Citrobacter freundiiCitrobacter freundii Citrobacter freundii Citrobacter freundii Citrobacter freundiiCitrobacter freundii and and and Salmonella typ Salmonella typ Salmonella typ Salmonella typ hi are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against are very sensitive against this this molecule moleculemoleculemolecule unlike Enterobacter cloac unlike Enterobacter cloac unlike Enterobacter cloac unlike Enterobacter cloac unlike Enterobacter cloacunlike Enterobacter cloac unlike Enterobacter cloac unlike Enterobacter cloac unlike Enterobacter cloacae bacteria which is resistant)ae bacteria which is resistant)ae bacteria which is resistant) ae bacteria which is resistant)ae bacteria which is resistant)ae bacteria which is resistant) ae bacteria which is resistant) ae bacteria which is resistant)ae bacteria which is resistant) ae bacteria which is resistant) ae bacteria which is resistant) ae bacteria which is resistant) .
artical
Keywords: ProlineProline ; complex; ligand; Schiff base; bactericidal activity; inhibitor.complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor.complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor.complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor.complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor.complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor.complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex; ligand; Schiff base; bactericidal activity; inhibitor. complex